Ethanol Oxidation on TiOxCy‐Supported Pt Nanoparticles. Issue 11 (24th May 2013) - Rüdiger, Celine; Brumbarov, Jassen; Wiesinger, Florian; Leonardi, Silvia; Paschos, Odysseas; Vidal, Carlos Valero; Kunze‐Liebhäuser, Julia
<x xml:space="preserve">Abstract</x> Plane sailing: Planar TiOxCy films are used as model supports for Pt nanoparticles for ethanol oxidation at 25–80 °C. The highest steady‐state current density of Pt on TiOxCy at 80 °C was a factor of 170 higher than that of Pt on glassy carbon.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>